2020
DOI: 10.1186/s12886-020-01489-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-182-5p protects human lens epithelial cells against oxidative stress-induced apoptosis by inhibiting NOX4 and p38 MAPK signalling

Abstract: Background MicroRNAs (miRNAs) are abnormally expressed in various ocular diseases, including age-related cataract. However, the role of miR-182-5p in the progression of age-related cataract remains unclear. Methods The expression of miR-182-5p in HLE-B3 cells was detected by qRT-PCR. HLE-B3 cells were transfected with miR-182-5p mimics. CCK-8, EdU, flow cytometry, 2′,7′-dichlorodihydrofluorescein diacetate, JC-1 kit, and western blot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Given that H 2 O 2 -induced oxidative stress can lead to a dose-dependent decrease of cell viability in various other cell types 15 , 16 , we sought to verify whether H 2 O 2 can induce the death of photoreceptor cells in a dose-dependent manner. To this end, we determined the optimal concentration of H 2 O 2 that could be used to establish an in vitro model of RDDs using the mouse retinal cone 661w cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Given that H 2 O 2 -induced oxidative stress can lead to a dose-dependent decrease of cell viability in various other cell types 15 , 16 , we sought to verify whether H 2 O 2 can induce the death of photoreceptor cells in a dose-dependent manner. To this end, we determined the optimal concentration of H 2 O 2 that could be used to establish an in vitro model of RDDs using the mouse retinal cone 661w cell line.…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are a class of small noncoding RNAs (~22 nt) that can modulate the transcription of genes (7,8). Previous studies have reported that abnormal expression of miRNAs is involved in cataracts development (9,10). For example, miR-34 facilitates apoptosis of lens epithelial cells via transforming growth factor (TGF)-β/Smads signaling (11).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have recently reported a link between OxS and miRNAs, the pivotal regulators of different aspects of glucose homeostasis, such as peripheral insulin signaling, β-cells function, lipogenesis, and chronic inflammation [6,[11][12][13][14][15]. For instance, miRNAs directly and indirectly influence he expression level or activity of antioxidative defense genes or ones generating ROS, thereby having an impact on redox balance [16][17][18][19][20][21][22][23]. Moreover, ROS potently affect miRNAs expression levels [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%